2015
DOI: 10.1007/s10853-015-9082-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of efficient magnetic biosorbents by clicking carbohydrates onto graphene oxide

Abstract: In this work, hydrophilic graphene nanosheets (GNS) and the related magnetic nanocomposites were prepared by first tethering alkyne-functionalized graphene oxide (GO) with azide-modified glucose followed by deposition of Fe 3 O 4 nanoparticles on the functionalized GNS. For the preparation of nanohybrids, two approaches were designed: in the first one, after chlorination of GO with thionyl chloride, GO was reacted with propargyl alcohol and subsequently clicked with azideglucoside. The resulted sweet GNS were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…We have reported carbohydrate and magnetic nanoparticles attachment onto GO via click-reaction3335. To our knowledge, there are not many reports on using ‘grafting from’ method, RAFT-polymerization and click reaction together to prepare graphene nanocomposites.…”
mentioning
confidence: 99%
“…We have reported carbohydrate and magnetic nanoparticles attachment onto GO via click-reaction3335. To our knowledge, there are not many reports on using ‘grafting from’ method, RAFT-polymerization and click reaction together to prepare graphene nanocomposites.…”
mentioning
confidence: 99%
“…It is possible that functionalization of GO with MCT‐β‐CD could have led to the formation of graphite‐like platelets. Compared with GO, the XRD pattern of the GO‐MCT‐β‐CD showed some new peaks at 2θ=32° and 45.5°, corresponding to MCT‐β‐CD pattern and indicating that the attachment of MCT‐β‐CD occurred to the GO support …”
Section: Resultsmentioning
confidence: 85%
“…The same research group later on reported on an extension of their first work on “sweet-graphene” in which they employed two different CuAAC click-reactions in order to achieve basal plane and edges functionalization of GO with glucose. (see Figure 8 ) [ 56 ]. In a similar fashion as before, this required the pre-alkyne modification of GO at the edge -COOH entities or at the -OH basal plane entities ( Figure 8 ).…”
Section: Covalent Conjugation Of (Poly)saccharides To Graphenementioning
confidence: 99%